Noun phrases, pronouns and anaphoric reference in young children narratives - Gülzow, Insa; Gagarina, Natalia Vladimirovna (ZAS Papers in Linguistics, 2007)
This paper deals with the development of discourse competence in German-, Russian- and Bulgarian-speaking children. In particular, it examines the use of anaphoric pronominal reference in elicited narrations of children between the ages of 2;6 and 6;0. As the pronominal (and nominal) systems of target German, Russian and Bulgarian differ in the repertoire and functions of anaphoric elements we will examine which kind of noun phrases children use to make reference to story participants. In a second step of the analysis, we will investigate how pronominal expressions relate to antecedents. In this respect the pronominal form of the anaphor, the syntactic function of the antecedent and the distance between antecedent and anaphor will be analyzed. The findings will be discussed with regard to predictions made by proposals such as the Complementary Hypothesis (Bosch, Rozario, and Zhao 2003) which assumes an asymmetry between the use of personal pro-nouns and demonstrative pronouns when referring back to subject or object antecedents.